RELIGIOSITY AND SUBJECTIVE WELL-BEING TOWARDS A BALANCED CIVILIZATION: A STUDY AMONG MUSLIM OLDER ADULTS IN MALAYSIA - Achour, Meguellati; Ab Halim, Asyiqin Binti; Haj Ali, Ahmed Raja; Sa’ari, Che Zarrina Binti; Al-Nahari, Ameen Ahmed Abdullah Qasem (Journal of Al-Tamaddun, 2019)
The aim of this conceptual paper is to shed more light on the significant of religiosity as a psychosocial determinant of elderly subjective well-being, and its role of as a resource copping strategy, social support, and meaning to life experience. This paper draws on the observation of other scholars in the relationship of religion to health, happiness and well-being research. The deductive and exploratory approach was used to select, analyze and summarize the related literature. The literature indicates that religiosity is associated with elderly people life satisfaction, happiness, and self-esteem. Religious affiliation buffers negative effects of stress on physical health; Prayer buffers the effects of stress on depressive. The paper reviewed the literature on both concepts of well-being and religiosity from Malaysian context. Highlighting the issue of the increase in population of people aged 60 and above, who will need an extra care.